Glutamate receptor activation is involved in 5-HT2 agonist-induced Arc gene expression in the rat cortex. - Pei, Q; Tordera, R; Sprakes, M; Sharp, T (2004)
Brain 5-HT regulates the expression of gene transcription factor as well as novel effector immediate early genes (IEGs). The 5-HT regulation of the gene transcription factor IEG, c-fos, involves activation of 5-HT2A and ionotropic glutamate receptors. Here, we investigate whether these receptors are also involved in the regulation of the effector IEG, Arc. In rats, the 5-HT2 agonist DOI induced a marked increase in expression of Arc mRNA in a variety of cortical regions. This effect was blocked by the selective 5-HT2A receptor antagonist, MDL 100,907, but not the 5-HT(2B/2C) receptor antagonist, SB206553. The AMPA receptor antagonist GYKI 52466 also attenuated DOI-induced Arc mRNA expression, as did the NMDA receptor antagonist MK801 in some regions. Immunofluorescence studies showed that DOI increased Arc-immunoreactivity in cortical cells that expressed AMPA and NMDA receptor subunits but not the 5-HT2A receptor. Finally, DOI-induced Arc-immunoreactivity in cortical cells was extensively co-localised with c-fos-immunoreactivity. These results suggest that, as with c-fos expression, ionotropic glutamate receptors (AMPA and NMDA) are involved in 5-HT2A receptor-induced Arc expression. This finding, together with evidence of extensive Arc and c-fos co-localisation, suggests that 5-HT2A receptor activation may induce the expression of both effector and transcription factor IEGs via common molecular and cellular substrates.